2011
DOI: 10.1371/journal.pntd.0001323
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase-Expressing Leishmania infantum Allows the Monitoring of Amastigote Population Size, In Vivo, Ex Vivo and In Vitro

Abstract: Here we engineered transgenic Leishmania infantum that express luciferase, the objectives being to more easily monitor in real time their establishment either in BALB/c mice—the liver and spleen being mainly studied—or in vitro. Whatever stationary phase L. infantum promastigotes population—wild type or engineered to express luciferase—the parasite burden was similar in the liver and the spleen at day 30 post the intravenous inoculation of BALB/c mice. Imaging of L. infantum hosting BALB/C mice provided sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 19 publications
(17 reference statements)
0
51
1
1
Order By: Relevance
“…4). In all cases, the ANBs screened had no growth-inhibitory effect against this mammalian line at concentrations of up to 100 M. Comparison of the mammalian cell IC 50 with the equivalent value obtained against amastigote parasites revealed that CB1964 and NH11 displayed Ͼ2,000-and Ͼ1,667-fold selective toxicity toward the intracellular pathogen, respectively. This clearly demonstrates that the antiparasitic activity displayed by these two compounds was specifically due to growth inhibition of L. major and not due to induction of host cell toxicity.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…4). In all cases, the ANBs screened had no growth-inhibitory effect against this mammalian line at concentrations of up to 100 M. Comparison of the mammalian cell IC 50 with the equivalent value obtained against amastigote parasites revealed that CB1964 and NH11 displayed Ͼ2,000-and Ͼ1,667-fold selective toxicity toward the intracellular pathogen, respectively. This clearly demonstrates that the antiparasitic activity displayed by these two compounds was specifically due to growth inhibition of L. major and not due to induction of host cell toxicity.…”
Section: Resultsmentioning
confidence: 93%
“…This screening demonstrated that cells expressing lower levels of the oxidoreductase were between 2-and 4-fold more resistant to the ANB than controls; wild-type L. major had IC 50 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This 'bioluminescent approach' highlighted the well-characterized liverto-spleen parasite colonization. Furthermore, this model was used to study the effect of miltefosine, showing that 5 days after treatment both parasite load and the luminescence signal were undetectable in spleen or lymph nodes [29].…”
Section: Reviewsmentioning
confidence: 99%